New Light on Chloroplast Redox Regulation: Molecular Mechanism of Protein Thiol Oxidation - Yoshida, Keisuke; Yokochi, Yuichi; Hisabori, Toru (Frontiers in Plant Science, 2019)
Thiol-based redox regulation is a posttranslational protein modification that plays a key role in adjusting chloroplast functions in response to changing light conditions. Redox-sensitive target proteins are reduced upon illumination, which turns on (or off in a certain case) their enzyme activities. A redox cascade via ferredoxin, ferredoxin-thioredoxin reductase, and thioredoxin has been classically recognized as the key system for transmitting the light-induced reductive signal to target proteins. By contrast, the molecular mechanism underlying target protein oxidation, which is observed during light to dark transitions, remains undetermined over the past several decades. Recently, the factors and pathways for protein thiol oxidation in chloroplasts have been reported, finally shedding light on this long-standing issue. We identified thioredoxin-like2 as one of the protein-oxidation factors in chloroplasts. This protein is characterized by its higher redox potential than that of canonical thioredoxin, that is more favorable for target protein oxidation. Furthermore, 2-Cys peroxiredoxin, and hydrogen peroxide are also involved in the overall protein-oxidation machinery. Here we summarize the newly uncovered “dark side” of chloroplast redox regulation, giving an insight into how plants rest their photosynthetic activity at night.